Answer:
csc(-112°)=-csc(68°)
Step-by-step explanation:
Since cosec(x) and sin(x) are reciprocals of each other,
cosec(-112°)=![\frac{1}{sin(-112^{\circ})}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bsin%28-112%5E%7B%5Ccirc%7D%29%7D)
=![\frac{1}{-sin(112^{\circ})}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B-sin%28112%5E%7B%5Ccirc%7D%29%7D)
=
(since 112=180-68)
=
(since sin(180-x)=sinx)
=
(since
)
=-cosec(68°)
Answer:
72.3 - 39.1 = 4tens - 7ones + 2tenth
Step-by-step explanation:
Give the expression 72.3 + (-39.1)
opening the parenthesis:
= 72.3 + (-39.1)
= 72.3 - 39.1
Breaking the decimal values into place values
72.3 = 7tens + 2units + 3tenth
72.3 = 7(10)+2(1)+3(1/10)
72.3 =70+2+0.3
Similarly for 39.1
39.1 = 3tens + 9units + 1tenth
39.1 = 3(10)+9(1)+1(1/10)
39.1 =30+9+0.1
72.3 - 39.1 = 70+2+0.3 - (30+9+0.1)
72.3 - 39.1 = 70+2+0.3 - 30-9-0.1
72.3 - 39.1 = 70-30+2-9+0.3-0.1
72.3 - 39.1 = 40 - 7 +0.2
72.3 - 39.1 = 4tens - 7ones + 2tenth
Answer:
![y=x^2+x-12](https://tex.z-dn.net/?f=y%3Dx%5E2%2Bx-12)
Step-by-step explanation:
f(x) = x² – 8 and g(x) = 4-x
y=f(x) - g(x)
y=(x² – 8) - (4-x)
![y=x^2-8-4+x\\y=x^2+x-12](https://tex.z-dn.net/?f=y%3Dx%5E2-8-4%2Bx%5C%5Cy%3Dx%5E2%2Bx-12)
Answer:
WANNA HEAR SOME METAL
Step-by-step explanation:
WANNA HEAR ME ROAAAAAAAAAAAAAAAAAR
425 / 50 = 8,5
There you go.